Induction of epithelial–mesenchymal transition and loss of podoplanin expression are associated with progression of lymph node metastases in human papillomavirus‐related oropharyngeal carcinoma1. Issue 6 (10th November 2014) - Wakisaka, Naohiro; Yoshida, Shinya; Kondo, Satoru; Kita, Makiko; Sawada‐Kitamura, Seiko; Endo, Kazuhira; Tsuji, Akira; Nakanish, Yosuke; Murono, Shigeyuki; Yoshizaki, Tomokazu
<x xml:space="preserve">Abstract</x> Aims To examine human papillomavirus (HPV) status, the expression of podoplanin and epithelial–mesenchymal transition (EMT) markers and lymphatic vessel counts (LVC) in oropharyngeal squamous cell carcinoma (OPSCC) tissues, and to evaluate whether these factors were associated with survival and nodal status. Methods and results A total of 53 OPSCC specimens were evaluated for HPV status and expression of proteins such as podoplanin and EMT markers by immunohistochemistry. E‐cadherin‐negative and vimentin‐positive specimens were defined as EMT‐positive. Twenty‐two OPSCCs were HPV‐positive. There was significant progression of nodal status in patients with HPV‐positive tumours (P = 0.0475). HPV‐positive cases had significantly lower expression of podoplanin (P = 0.0016) and were more frequently EMT‐positive (P = 0.0172). Podoplanin‐negative cases and EMT‐positive cases showed significantly more advanced nodal status than their respective counterparts (P = 0.0082 and P = 0.0186, respectively). LVC correlated with neither HPV nor nodal status. Multivariate analyses revealed that HPV infection was an independent marker of longer disease‐specific survival (P = 0.014). Conclusions HPV‐positivity in OPSCC was associated with loss of podoplanin expression and with EMT induction, which resulted in progression of nodal status. The mechanisms leading to an improved prognosis in HPV‐positive OPSCC patients requires elucidation, as this is inconsistent with the aggressive phenotype with lymph node metastases.